The brethren [anglicky] - Grisham, John, 1955- (Arrow Books, 2000)
They call themselves the Brethren: three disgraced former judges doing time in a Florida federal prison. One was sent up for tax evasion. Another, for skimming bingo profits. And the third, for a career-ending drunken joyride. Meeting daily in the prison law library, taking exercise walks in their boxer shorts, these judges-turned-felons can reminisce about old court cases, dispense a little jailhouse justice, and contemplate where their lives went wrong. Or they can use their time in prison to get very rich very fast.And so they sit, sprawled in the prison library, furiously writing letters, fine-tuning a wickedly brilliant extortion scam ... while events outside their prison walls begin to erupt. A bizarre presidential election is holding the nation in its grips and a powerful government figure is pulling some very hidden strings. For the Brethren, the timing couldn't be better. Because they've just found the perfect victim...